Optimalisasi pelayanan pensiunan Asabri di PT. Pos Indonesia KCP Krembangan - Zahra Aini Nasyifa; Ira Wikartika (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
Asabri pension services through the submission of the Statement of Proof of Identity (SPTB) constitute an essential component of public services, as they directly affect the continuity of pension benefit disbursement. Along with the implementation of digital transformation through the Asabri Mobile application, the reporting process requires users to have sufficient technical understanding to conduct identity verification, data entry, and document uploads independently. However, in practice, many pensioners experience difficulties due to limited digital literacy, particularly among elderly users. This condition is evident in service implementation at PT Pos Indonesia KCP Krembangan, which serves as a frontline service unit providing direct assistance to pensioners during the reporting process. This community service activity aims to optimize SPTB reporting services through structured and direct assistance in using the Asabri Mobile application. The implementation method involved direct engagement in service activities, field observation, and technical assistance to pensioners throughout the reporting process. The results indicate that systematic assistance improves the smoothness of reporting, reduces data upload and verification errors, and enhances pensioners’ understanding of application procedures. In conclusion, optimizing digital public services requires the active role of service officers in providing inclusive, adaptive, and user-oriented assistance tailored to the needs of elderly pensioners.